2014
DOI: 10.1093/eurpub/cku005
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and mental health scarring during the life course

Abstract: There are long-term mental health scarring effects of exposure to youth unemployment and multiple exposure to unemployment during the life course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
162
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(181 citation statements)
references
References 25 publications
12
162
3
4
Order By: Relevance
“…4 Previous research on the same cohort has shown a significant association for both women and men between recent unemployment and several health measures, 29 and between youth unemployment and internalized mental health symptoms in adulthood. 9 In this study, there were no significant associations for women between youth unemployment and functional somatic symptoms, even though women tend to score higher than men on functional somatic symptoms.…”
Section: On the Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…4 Previous research on the same cohort has shown a significant association for both women and men between recent unemployment and several health measures, 29 and between youth unemployment and internalized mental health symptoms in adulthood. 9 In this study, there were no significant associations for women between youth unemployment and functional somatic symptoms, even though women tend to score higher than men on functional somatic symptoms.…”
Section: On the Resultscontrasting
confidence: 60%
“…27 Earlier analyses on our cohort showed long-term association of youth unemployment with mental health in adulthood. 9 These previous studies have only examined long-term unemployment (6 or 12 months of unemployment). Our study indicates that each month in youth unemployment is associated with a higher level of functional somatic symptoms in adulthood for men.…”
Section: On the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A few previous studies on the long-term health consequences mostly examine the general population (Daly & Delaney, 2013;Schröder, 2013). However, recent evidence from long-run cohort studies suggests that young people may be particularly vulnerable to the negative effects of unemployment (Bell & Blanchflower, 2011;Strandh, Winefield, Nilsson, & Hammarström, 2014). There are a number of potential explanations for these findings.…”
Section: Introductionmentioning
confidence: 99%
“…2 Following recent interest in the mechanisms behind the negative long-term effects of job loss and unemployment on health (e.g. Strandh et al, 2014), we additionally examine how the subsequent unemployment risks and employment instability mediate this relationship. Although the previous empirical evidence is scarce (see Brydsten et al, 2015 for an exception), theoretically, a life course perspective is often employed arguing that initial disadvantages produce further relative disadvantages over time (e.g.…”
Section: Introductionmentioning
confidence: 99%